К типологической классификации словосочетаний курдского языка - Хамоян, Максим (Ասողիկ հրատ.)
The paper deals with one of the unsolved problems of theoretical syntax in modern Kurdish language on the basis of syntactical material sollected by the author. The subject matter is the revelation and the content schemes of syntactical word-combination and ihe character of the mutual relations existing between them. The outcome of the research work gives eveiy reason to bring to light the oerall composition of the word combination, pattern which enables to represent the structural-semantical typology of word-combinations and thejr grammalical Orders.
Keywords: Лингвистика; Курдский язык